Wingate test as a strong predictor of 1500-m performance in elite speed skaters - Hofman, N.; Orie,J.; Hoozemans, M. J. M.; Foster, C.; de Koning, J. J. (International Journal of Sports Physiology and Performance, 2017)
Wingate test scores are strongly associated with anaerobic capacity in athletes involved in speed-endurance sports. In speed skating Wingate results are known to predict performance cross-sectionally but have not been investigated relative to their ability to predict performance longitudinally. Purpose: To investigate whether Wingate tests performed during summer training are predictive of 1500-m speed-skating performance the subsequent winter in elite speed skaters. Methods: Wingate test results from the summer training periods and 1500-m performances during the subsequent winter were analyzed over a 3-y period in 5 female and 8 male elite (Olympic, World Championship, and World Cup medalists) speed skaters. Regression analyses using generalized estimating equations (GEE) were used to estimate the relationship between Wingate test variables and 1500-m speed-skating performance. Wingate peak power (PP) and mean power (MP) were used to predict 1500-m time and 400-m lap times. Results: Improvements of 1 W/kg on PP and MP in women predict improvements of -0.75 s and -2.05 s, respectively, on 1500-m time (World Record 110.85 s). In men, improvements in PP and MP were associated with performance improvements of -0.92 s and -2.32 s on 1500-m time per 1 W/kg (World Record 101.04 s). Conclusion: Wingate test results achieved during the summer training period are a good predictor of improvements in 1500-m speed-skating performance during the subsequent winter. For the smallest worthwhile improvement in 1500-m performance, a gain in PP and MP of 2.1% and 1.4% (0.38 and 0.14 W/kg) for females and 1.2% and 0.9% (0.29 and 0.12 W/kg) for males is needed.